Ijaz Ilmi Pada Ayat-Ayat Al-Quran - Idris Siregar; Adellia Fitriani; Siti Mardiana (Jurnal Budi Pekerti Agama Islam, 2024)
I'jaz ilmi" is one of the miracles of the Koran related to science, which appeared during the revival of science among Islamic Muslims, and greatly motivated its followers to study continuously. Even science is considered important. The earliest verses of the Qur'ân are the most fascinating references and the most important facts on the subject, because they encouraged people to explore and uphold this knowledge. In the Qur'an, the words "sama" and "bashar" often appear in the same verse, but usually the word "sama" comes first. The author found and collected data about the research object, namely the words sama and bashar, using a qualitative approach. The study reached several conclusions, one of which was that the words "sama" and "bashar" are mentioned thirty-four times in the Quran.